(untitled) (Global Conference on Medical and Health Sciences, 2026)
Reforms underway in Uzbekistan’s higher education system are closely linked to the “Digital Uzbekistan – 2030” strategy, and in this process the higher education management information system—HEMIS—is taking shape as a central infrastructure. With HEMIS, it becomes possible to plan the educational process, monitor students’ academic performance, account for faculty workload, and manage contracts and financial operations in a digital environment. This thesis analyzes HEMIS’s functional role in digitalizing higher education, its place within the mobile application and an integrated digital ecosystem, as well as challenges related to technical infrastructure, digital competencies, and information security, and directions for addressing them. The impact of digital transformation on education quality, management efficiency, and transparency is briefly summarized based on existing research and regulatory documents.